The Divorcement Family Career in the Religious Court in the Region of the Bandung High Court of Religion with its Relationship Articles 33-34 in Law of the Republic of Indonesia Number 1 of 1974 Marriage - Muhammad Sopiyan; Tajul Arifin; Muhammad Saran (Dinasti Research, 2024)
Articles 33-34 of Law Number 1 of 1974 concerning Marriage state that the husband is obliged to provide for the family while the wife must help with household affairs. However, many wives have careers outside the home, so the intended article is not implemented properly, eventually leading to marital disputes that end in divorce. Against the background of this problem, four questions were asked, namely (1) what are the factors that cause divorce in career families in the decision of the Religious Court in the Bandung Religious High Court; (2) how does the panel of judges consider in deciding a career family divorce in the religious court of the Bandung PTA area; (3) how to implement Articles 33-34 of the Marriage Law based on the Decision of the Religious Court in the Bandung PTA Region among career families; and (4) how is the development of the concept of a harmonious family in the career family related to the implementation of articles 33-34 in Law Number 1 of 1974 on Marriage? The usefulness of this research is academically to develop family law studies, while practically adding new insights and findings in divorce issues that are useful for society educational.